Karakteristik dan kandungan mineral pasir pantai Lhok Mee, Beureunut dan Leungah, Kabupaten Aceh Besar - Saniah .; Syahrul Purnawan; Sofyatuddin Karina (Depik, 2014)
Abstract. The objective of this research was to determine the characteristics and mineral content of coastal sand from Lhokmee, Beureunut, and Leungah Aceh Besar District. The sand analysis was conducted at Material Laboratory of Mathematics and Natural Sciences Faculty, Syiah Kuala University from March to April, 2014. Samples were collected using purpossive sampling method. The observed physical characteristics of this research were sand color, shape and particle size. The mineral content was analysed using X-Ray Diffraction (XRD) and Joint Committee for Powder Diffraction Standard (JCPDS) program. The result showed that Lhok Mee coastal sand was physically characterized as white, sub-angular rounded shape and 0.21 mm of size, while Beureunut coastal sand was light brown, rounded-well rounded shape and 0.19 mm of size, then Leungah coastal sand was black, angular-well rounded shape and 0.13 mm of size. Based on mineral content showed that Lhok Mee, Beureunut, and Leungah coastal sand were dominated by SiO3, SO3 and Fe3O4, respectively. All identified minerals at all stations were classified as volcanic minerals of lithogenous sediment. Keywords: Beach sands; Color difference; Mineral content; Shape; Particle size.